IMPLEMENTATION OF STEGANOGRAPHY ON DIGITAL IMAGE WITH MODIFIED VIGENERE CIPHER ALGORITHM AND LEAST SIGNIFICANT BIT (LSB) METHOD - Gilang Miftakhul Fahmi; Khairunnisak Nur Isnaini; Didit Suhartono (Jurnal Teknik Informatika (Jutif), 2023)
Digital image can be utilized as a media to hide messages. There should be a special treatment in securing the messages so that the information accessibility can be controlled. Hiding messages to an image can be conducted using steganography. It can be combined with cryptography algorithms in order to make it harder to be accessed by unauthorized parties. The modification of cryptography algorithms can improve the confidentiality of the message content. This research is aimed to know the implementation of steganography in desktop applications using Least Significant Bit (LSB) that is combined with the modification of Vigenere Cipher algorithms. The developed software namely waterfall supports the creation of applications. The result of the research shows that the encrypted picture will change into gray or display in grayscale so that the hidden message will be more difficult to be accessed by the attacker. The encrypted picture will also have a bigger size file than the original version and the extended file. The LSB method will work precisely according to the formula of the modified cryptography algorithm. The further research is suggested to focus on the variation of media for content message and the picture format in their encryption.